Чевенгур: Роман / А. П. Платонов - Платонов Андрей Платонович (Худож. лит., 1988)
Экземпляры: п/ф (ретроконверсия) / Инвентарный номер: 24246 / Цена: 3.00 / Сис.шифр: Р2 / Авт.знак: П37 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6